The influence of leader member exchange on employee performance with employee engagement as a mediator - Sonya Nurfelia Syafrina; Sulastri Sulastri (Universitas Negeri Padang, 2021)
This research has purpose to analyzed: (1) influence of leader member exchange on employee performance at PT Sumatra Tropical Spices (2) influence of leader member exchange on employee engagement at PT Sumater Tropical Spices. (3) influence of employee engagement on Employee Performance at PT Sumatra Tropical Spices. (4) influence of leader member exchange on employee performance at PT Sumatra Tropical Spices. This research is classified as a causal research. The population in this study were all employees of PT Sumatra Tropical Spices with a total of 156 people. The sample size is determined using the Slovin formula found as many as 112 respondents and sampling in this study using proporsional clustered simple random sampling. Collecting data using questionnaire with Likert scale. The analysis technique used is PLS-SEM analysis. This research found that: (1) There is a positive and significant direct influence between leader member exchange and employee performance at PT. Sumatra Tropical Spices, (2) There is a positive and significant direct influence between leader member exchanges on employee engagement at PT. Sumatra Tropical Spices. (3) There is a positive and significant direct influence between employee engagement and employee performance at PT. Sumatra Tropical Spices. (4) There is a positive and significant indirect effect between leader member exchanges on employee performance through employee engagement as a mediating variable at PT. Sumatra Tropical Spices